Studi Eksploratif Mengenai Karakteristik dan Faktor Pembentuk Identitas Etnik Sunda - Agus Abdul Rahman; Sarbini Sarbini; Tarsono Tarsono; Elis Anisa Fitriah; Agus Mulyana (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2018)
Jawa Barat is one of the provinces with strong cultural identity. Nowadays, several districts in West Java seek to strengthen their cultural identity in various ways. This study explores the characteristics and factors that shape the identity of Sundanese. The study was conducted in one of the districts in West Java that are intense in maintaining and developing Sundanese culture. Respondents consisted of 639 students in seventeen schools. Data were collected using questionnaires and interviews. The results show that the ethnic identity of the respondents was above average. Most respondents have reached the “achieved” stage, which is marked by strong exploration and commitment. Factors influencing the ethnic identity of respondents include gender, parent education, and the use of Sundanese as the native language. Sundanese ethnic characteristics are mentioned by many respondents, among others, polite and polite, friendly or “someah,” solider and like mutual help, compassionate, sociable, and religious.